PAREGREG DALAM SEBUAH MONUMEN - Tjahjono, Baskoro Daru (Berkala Arkeologi, 1999)
At the time when the Hindu kingdoms were still in power in Indonesia, the establishment of sima was often associated with the services that the people of a village had given to their king. To commemorate this event, a sacred building was erected, and the village community concerned was obliged to maintain it. Due to the burden of maintaining the sacred building, the village community was exempted from the obligation to pay taxes to the king. A building that was recently found in Dukuh Centong, Sawentar Village, Kanigoro District, Blitar Regency is possibly an example of a building that is a memorial to an important event during the Majapahit era. Although the building is not very big, it is very interesting to study, especially if it is related to its historical background and rare architectural form.